KINETICS OF DAPAGLIFLOZIN 10 MG IMMEDIATE RELEASE TABLET IN HEALTHY CAUCASIAN VOLUNTEERS: DOES FOOD INTAKE AFFECT ITS DISPOSITION IN THE BODY? - OROIAN, Monica; VLASE, Ana-Maria; MARCOVICI, Adriana; VLASE, Laurian (Studia Universitatis Babeș-Bolyai Chemia, 2023)
The aim of the current study was to investigate whether food intake alters the kinetics of dapaglliflozin, a modern anti-diabetic agent, after single-dose oral administration of a new 10 mg immediate release tablet. The evaluated formulation was developed and manufactured by Sun Pharmaceutical Industries Limited, India, and the studies were performed in healthy Caucasian subjects. The data obtained during the fasting and fed bioequivalence studies were analyzed to observe the influence of food on the bioavailability and disposition of the evaluated formulation. Although differences were observed between studies concerning some of the main parameters that describe dapagliflozin’s disposition (maximum plasma concentration – Cmax, and the time to reach it -Tmax), they were proved bioequivalent. The 90% confidence intervals for the evaluated parameters were within the accepted range of 80.00-125.00% for bioequivalence conclusion, therefore the treatments are bioequivalent (dapagliflozin with/without food) and interchangeable. Hence, dapagliflozin can be administered regardless of food intake in diabetic patients.